Local And Deep-Ocean Forcing Effects on the West Florida Continental Shelf Circulation and Ecology - Weisberg, Robert H.; Liu, Yonggang (Frontiers in Marine Science, 2022)
We review the evolution of knowledge on the forcing of the west Florida continental shelf by a combination of local winds and deep-ocean influences, and we provide application examples regarding the relationships between the shelf responses to these forcing functions and certain ecological phenomena, including blooms of the harmful alga, Karenia brevis, recruitment of gag juveniles and how Deepwater Horizon hydrocarbons may have affected west Florida reef fish and the shoreline. Our approach employs a coordinated set of observations and numerical circulation model simulations, wherein the observations, by providing reasonable veracity checks on the model simulations, allow for further dynamical analyses that would otherwise be unavailable from the observations alone. For the case of local forcing only, we provide two dynamically consistent definitions of the inner-shelf and outer-shelf regions, and for the case of deep-ocean forcing, we show how the west Florida shelf geometry (with regard to certain geophysical fluid dynamics principles) can result in the entire shelf region being impacted by the Gulf of Mexico Loop Current. Thus, we help to explain why the west Florida shelf experiences large inter-annual variations in shelf ecology, providing impetus for further interdisciplinary study.